Knowledge on Perimenopausal Symptoms among Women Attending Lumbini Medical College Teaching Hospital - Paudyal, Parbati Nepal; Nepal, Manju (Journal of Lumbini Medical College, 2016)
Introduction: Perimenopause is an unavoidable stage of a woman’s reproductive life that starts several years before menopause. Due to declining estrogen level, women experience physiological and psychological changes during perimenopausal period and sometimes symptoms are very distressing that affect the women’s quality of life negatively. This study was done to assess the knowledge of women about perimenopausal symptoms.Methods: A cross-sectional analytical study was done at Lumbini Medical college (LMC) throughout the months of November and December, 2013. Women of age 40-60 years, attending various clinics in LMC and ready to take part in the study were included. A total of 142 women were selected purposefully. The data was collected using the semi structured interview schedule.Results: The study revealed that half of respondents were between age group 40-44 years, 141 (99.3%) were married and 82 (57.7%) were literate. Three quarter of respondents (74.6%) were menstruating women. The main source of information on perimenopausal symptoms was friends and relatives (81.2%). Majority of respondents (n=90, 63.4%) had poor, 52 (33.8%) had fair and only 2.8% had good level of knowledge on perimenopausal symptoms. The respondents’ level of knowledge on perimenopausal symptoms was statistically significant with educational status (p